Teneshwa beta keresityan : Ortodoksiyawi gabecha, betasab ena yahetsanat astadadag - Gebre Egziabher Kide. (Addis Ababa: : Gebre Egziabher Kide, 2013)
On Ethiopian Ortodox marriage and related issues.
Includes bibliographical references (pages [555]-567)
In Amharic.
Keywords: Ethiopian Ortodox Marriage